STOP SAYING VERY: AN EXCEPTIONAL TEACHING STRATEGY TO ENHANCE STUDENTS’ VOCABULARY MASTERY - Anna Stasya Prima Sari; Irmina Pinem; Dewi Anzelina; Rosa Maria Simamora; Lies Dian Marsa Ndraha (JETAL: Journal of English Teaching & Applied Linguistic, 2023)
This Classroom Action Research (henceforth, CAR) was primarily carried out to prove that the use of Stop saying very teaching strategy is effective to enhance the students’ vocabulary mastery on adjectives and to describe the students’ responses towards the learning teaching processes of adjectives through the application of Stop saying very teaching strategy. There are two cycles in this CAR in which each cycle consisted of three meetings excluded the pre-test, formative test, and post-test The research subjects of this CAR are the first semester students of the English Language Education, Faculty of Teachers Training and Education, Universitas Katolik Santo Thomas in the Academic Year of 2022/2023 consisting of 20 students. The analysis of quantitative data shows that the mean of the students’ score in the pre-test, formative test, and post-test increases continually after Stop saying very teaching strategy was implemented in teaching adjectives. The students’ total score in the pre-test is 216 and the pre-test mean is 10.8. The students’ total score in the formative test is 1.528 and the formative test mean is 76.4. The students’ total score in the post-test is 1.708 and the post-test mean is 85.4. The analysis of qualitative data shows that the students gave positive responses towards the learning teaching processes of adjectives through the application of Stop saying very teaching strategy. They all agree that the application of Stop saying very teaching strategy helps trigger their curiosity and enhance their knowledge and vocabulary mastery on adjectives. The writers recommend that English teachers/lecturers apply Stop saying very teaching strategy to teach better and more impressive adjectives to their students. Keywords: adjectives, stop saying very, teaching strategy, vocabulary mastery